Core knowledge about tuberculosis prevention and treatment among primary and middle school students and their parents in Heilongjiang province and correlation between students' and parents' knowledge level - Yong ZHOU; Shi-chun YAN; Lan YU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the awareness on core knowledge about tuberculosis (TB) prevention and control among primary and middle school students and their parents in Heilongjiang province and to analyze the correlation between the awareness of students and their parents for providing a reference to TB prevention and control and health education on TB in school and family settings.MethodsUsing stratified random cluster sampling, we recruited 1 255 pairs of primary and middle school students and their parents in 9 counties/districts of Heilongjiang province for a survey in August 2017. Based on the National Guideline for Implementation of TB Prevention and Control Plan - 2008, we compiled a questionnaire to collect relevant information among the participants.ResultsAmong all the students, the overall awareness rate of core knowledge about TB was 66.0% and the awareness rate differed significantly by gender and registered residence (both P < 0.05); for all of the parents, the overall awareness rate was 70.5% and there were significant differences in the education level- and registered residence-specific awareness rate of the parents (both P < 0.001). As for 6 items of core knowledge about TB, the students' and their parent' awareness rate were 85.7% and 92.5% for infectivity, 59.4% and 56.0% for route of transmission, 83.5% and 90.1% for clinical symptoms, 37.0% and 45.7% for designated medical institutions of TB treatment, 48.8% and 53.7% for reduction of TB patients' medical expenses, and 81.4% and 85.1% for treatment outcome, respectively. The results of Pearson correlation analysis revealed positive correlations between the students' knowledge and their parents' knowledge for all the 6 core knowledge about TB (all P < 0.001).ConclusionThe awareness rate of core knowledge about tuberculosis was low among primary and middle school students and their parents in Heilongjiang province and there is a positive correlation between the students' and their parents' core knowledge about tuberculosis.